2013
DOI: 10.1111/jebm.12017
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric off‐label drug use in China: risk factors and management strategies

Abstract: (i) A management guideline for off-label drug use is urgently needed, with which we can guide medical institutions to establish the management regulations of off-label drug use. (ii) Pediatric clinical research should be promoted actively, and pharmaceutical enterprises should be encouraged to completely provide pediatric drug information. (iv) Academic organizations should be invited to join in for best professional drug use. (v) Pediatric patients and their families should receive the education on rational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
0
17
0
5
Order By: Relevance
“…[4][5][6][7] Many studies have shown that neonates have higher risk of using off-label drugs than the children of other age groups. 6,[8][9][10][11] A range from 55 to 80% in the use of unlicensed or off-label drugs at neonatal settings is referred in literature reviews on this theme; the proportion of patients receiving at least one of these drugs ranges from 80-97%. 5,6,11 Other specificities of neonatology are the added risk of preterm newborns to die or develop serious morbidity throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Many studies have shown that neonates have higher risk of using off-label drugs than the children of other age groups. 6,[8][9][10][11] A range from 55 to 80% in the use of unlicensed or off-label drugs at neonatal settings is referred in literature reviews on this theme; the proportion of patients receiving at least one of these drugs ranges from 80-97%. 5,6,11 Other specificities of neonatology are the added risk of preterm newborns to die or develop serious morbidity throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficacy and safety of drugs used in the paediatric population, there is a need to increase research on new drugs and medications that are already on the market but have not been adequately adjusted for children. 22 Although several countries have encouraged protection against OLDU by authorizing a large number of new products with paediatric indications and ageappropriate pharmaceutical forms, 22 there is still an urgent need for regulations of OLDU not only for medical institutions but also for physicians, 23 as they are regularly confronted with questions of efficacy and safety, and ethical issues. 22 Patients will believe that all prescribed medicines have been approved by the country's regulatory agencies.…”
Section: Resultsmentioning
confidence: 99%
“…46 Neonates are the highest-risk paediatric population for off-label medicine use. 47 They require special consideration due to variables including prematurity and low birth weight affecting pharmacokinetics and pharmacodynamics. 10 An associated risk is the lack of child-appropriate dosage forms for medicine administration.…”
Section: Paediatricsmentioning
confidence: 99%